Developing a Classroom-based Language Assessment of Japanese for Children Who Speak Minority Languages in Japan: The Dialogic Language Assessment. Issue 5 (19th October 2020) - Butler, Yuko Goto; Sakurai, Chiho
ABSTRACT: One of the challenges of developing assessments for young language learners is the shortage of evidence-based information about such assessments for languages other than English. In light of this situation, this paper discusses the development of an assessment for young languages learners in the context of Japanese as a second language (JSL). In response to the growing number of young JSL learners (defined as children age 6–15) in Japanese schools, a JSL assessment called the Dialogic Language Assessment (DLA) has been developed and endorsed by the Japanese government. This paper discusses challenges and issues that emerged in the process of developing the content and format of the reading section of the DLA. The DLA has largely been developed through trial and error, and it has been revised based on the results of a series of pilot studies. A particular consideration is given to factors related to JSL students' age and educational and societal environments as well as to the unique aspects of the Japanese language (a nonalphabetical language). Because the DLA is a work in progress, this paper also discusses additional steps that need to be taken.